Daily Rhythms In Insecticide Susceptibility, Metabolic Enzyme Activity And Gene Expression In The Common Bed Bug, Cimex lectularius L. (Hemiptera: Cimicidae) - Khalid, Muhammad Fazli (2020)
The continuous usage of insecticides inadvertently leads to the development of insecticide resistance among insect pests including bed bugs. Several genes encoding enzymes known to metabolize insecticide such as Cytochrome P450, Glutathione S-tranferase (GST) and esterase are found to have daily rhythm in some insects such as mosquitoes, flies and cockroaches. To date, this information remains unclear in bed bugs. An improved understanding of bed bug chronotoxicity will yield insights into developing novel control strategies for this medically important pest species. To this extend, we explored daily rhythm in insecticide susceptibility of the common bed bug, Cimex lectularius.